The Elasticity of Health Expenditure on Agricultural Productivity Growth in Southeast Asia - Muhammad Muazu Bala; Shailender Singh; Hawati Janor (Asia Pacific Journal of Health Management, 2021)
Background: Recently, agricultural productivity growth has experienced a sharp downward turn across the countries of Southeast Asia partly due to population aging, increasing pace of urbanization, and industrialization.